Development and Challenges of STEAM Learning Implementation in Elementary Schools: A Comprehensive Literature Review - Erawan, Galih Majesty; Mariana, Neni; Suryanti, Suryanti (IKIP Widya Darma Surabaya, 2025)
Objective: This study is a comprehensive literature review on the development and challenges of STEAM learning implementation in elementary schools. Methods: The research method used is a literature review of articles and journals on Google Scholar in 2019-2024 totaling 10 articles that discuss the development and challenges of STEAM learning in elementary schools. Data analysis using qualitative descriptive methods. Results: The focus of the research is the development and challenges of STEAM implementation in elementary schools. The results showed that there are several developments in the implementation of STEAM learning in elementary schools with various new innovations in its application, ranging from the choice of topics, models, to the learning media used. The implementation of STEAM Learning develops by utilizing contextual learning that departs from real events in students' lives to collaborate and create a work, utilizing the surrounding environment as a learning tool (fertilizer making activities, JAKA games, sribu gymnastics exercises, and the implementation of mathematics in learning and students' daily lives), making projects that depart from the local wisdom of the area where students live (batik crafts), utilizing new technology (robots for learning activities), utilizing used material processing activities (Glass Bottle Music), utilizing innovative modules (“Beruang Antik” module), and also innovative learning media (Tak Tik Butarna Media). On the other hand, there are still various challenges in the process of implementing STEAM learning in elementary schools which include: pedagogical challenges, technical challenges, facility challenges, learning resource challenges and the timing of STEAM learning implementation. Novelty: The novelty of this research is that the literature review used is sourced from Google Scholar so that the results of the study can provide information about the development and challenges of STEAM implementation. This research focuses on what are the developments and challenges of implementing STEAM learning in elementary schools.